2021
DOI: 10.1080/23802359.2021.1917311
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the DNA molecular sequence of complete plastid genome of Paeonia rockii subsp. taibaishanica, an endemic species in China

Abstract: Paeonia rockii subsp. taibaishanica (Paeoniaceae), one of the tree peony species, is endemic to the Qinling Mountains in central China. In this study, we characterized its whole plastid genome sequence using the Illumina sequencing platform. The complete plastid genome size of P. rockii subsp. taibaishanica is 153,368 bp in length, including a large single copy (LSC) region of 85,030 bp, a small single copy (SSC) region of 17,042 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
1
1
Order By: Relevance
“…Onaepia . In contrast to previous studies [ 7 , 16 ], our findings suggest that sect. Onaepia represents the first branch to diverge from the ancient Paeonia lineage.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Onaepia . In contrast to previous studies [ 7 , 16 ], our findings suggest that sect. Onaepia represents the first branch to diverge from the ancient Paeonia lineage.…”
Section: Discussioncontrasting
confidence: 99%
“…Paeonia than to sect. Moutan , while Dong et al [ 16 ] reported opposite results. Thus, a more comprehensive plastome-based phylogenetic study is needed to provide new insight into the evolutionary history of Paeonia .…”
Section: Introductionmentioning
confidence: 99%